Studying of lipophilicity of potential biological active cyanoacetamide derivatives - Suzana Apostolov; Đenđi Vaštag (Journal of Engineering & Processing Management, 2017)
By applying the Lipinski's rule for selected cyanoacetamide derivatives the possible existence of biological activity is theoretically investigated. Alos,using appropriate software packages and applying reverse-phase thin-layer chromatography (RP TLC18 F 254s ) in water-t-butanol, water-dimethylformamide and water-dimethylsulfoxide the lipophilicity of the studied cyanoacetamides was determined. Chromatographic retention parameters, RM 0 and m, as presumed criteria of lipophilicity of examined cyanoacetamides were correlated by linear regression analysis with standard measure of lipophilicity, log P, with important pharmacokinetic predictors and selected parameters of toxicity. The established linear dependences are described by high regression coefficient values, r, which showed that RP TLC18 F 254s allows reliable determination of the lipophilicity of cyanoacetamides as potentially bioactive compounds.
Keywords: cyanoacetamides; lipophilicity; pharmacokinetic parameters; RPTLC; toxicity